Intensitas Modal dan Penghindaran Pajak Korporat: Tinjauan Literatur Sistematis dan Agenda Penelitian Masa Depan: Intensitas Modal dan Penghindaran Pajak Korporat: Tinjauan Literatur Sistematis dan Agenda Penelitian Masa Depan - Sasmita Isnan Fatony; Sylvia Azahra; Tiolina Evi Naustapardede (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
Corporate tax avoidance remains a critical issue for state revenue, reflected in the inconsistent effective tax rates of capital-intensive companies in Indonesia. Theoretically, capital intensity serves as a tax shield through depreciation expenses, yet empirical findings remain inconsistent. This study synthesizes prior empirical literature to unravel this paradox. Using a library research method employing systematic literature review, data were extracted from 17 academic works and one regulatory document, analyzed through content analysis and thematic synthesis. The synthesis of 13 empirical studies maps three patterns: five studies show a positive effect, supporting the tax shield hypothesis where fixed assets are opportunistically exploited to reduce taxable income; seven studies show no effect, as high fixed assets are purely driven by operational necessity; and one study shows a negative effect, consistent with the political cost hypothesis, where larger assets trigger stricter tax authority scrutiny, prompting firms to appear more compliant. This study also finds that corporate governance mechanisms, such as Good Corporate Governance, independent commissioners, and Corporate Social Responsibility, effectively curb tax avoidance among capital-intensive firms. These findings imply that tax oversight strategies should be tailored to each industry sector rather than generalizing all capital-intensive firms as high risk